Tolerance of high school students in an urban-transition city: a study in Batu City - Drajat Tri Kartono; Bagong Suyanto; Rahma Sugihartati; M. Turhan Yani; Mun’im Sirry; Theofilus Apolinaris Suryadinata; Bakat Jati Prasetyo; Lutfi Andriani (Cogent Education)
This study explores religious tolerance attitudes among high school students in Batu City, a city experiencing urban transition. Utilizing a qualitative case study approach, data were gathered through in-depth interviews with key informants, specifically student council presidents from five high and vocational schools selected through purposive sampling. These presidents are knowledgeable about school and community dynamics. Additional relevant informants from each school were also interviewed. A literature review incorporated previous research to enrich the analysis. The findings indicate that religious tolerance among high school students in Batu City requires improvement, with instances of intolerance stemming from ethnic, religious, and racial differences. However, religious literacy programs could promote critical thinking, dialogue, and understanding of religious diversity, thereby enhancing tolerance. Currently, the implementation of these programs lacks strategic planning, which allows intolerant attitudes to persist. The study emphasizes the significant roles of family, schools, peer environments, and social media in shaping effective religious literacy. It suggests that without a structured approach to religious literacy, intolerant behaviors may continue to arise. Well-designed programs could enhance students' awareness and tolerance, contributing to broader social harmony in urban transition areas like Batu City.